Preparation method of super hydrophobic Y-type molecular sieve
Through the method of treating the method of acid solution and rare earth, water and heat baking, acid exchange, and iron copper ion load, the problems of strong water sieve in the Y -shaped molecular sieve and many acidic positions have been solved. Production.
Patent Information
- Application Number
- CN202411451357.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-17
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieves, and in particular to a method for preparing a super-hydrophobic Y-type molecular sieve. Background Art
[0002] Y-type molecular sieve has many uses and a wide range of applications. Y-type molecular sieve has a large specific surface area and an appropriate pore size distribution. It can be used as a catalyst or catalyst carrier, such as hydrocracking, isomerization, alkylation, etc., and plays an important role in the reaction process. It also plays an important role in the fields of petrochemicals, environmental protection, etc. Y-type molecular sieve has a high adsorption capacity and can adsorb moisture, gas, liquid and other substances. It is widely used in the fields of desiccant, adsorbent, etc. Y-type molecular sieve can be used in the fields of medicine, water treatment, food, etc. to achieve the removal or exchange of specific ions. Y-type molecular sieve can also be used to make gas sensors, humidity sensors, etc.
[0003] Patents CN202010125447.7, CN201911169265.3, CN202310150176.4; are all modification technology solutions for Y-type molecular sieves. In the above solutions, the use of organic solvents is involved. The silanization treatment of organic solvents will cause pollution to water resources, and the subsequent treatment of organic solvents will cause pressure on the atmospheric environment. Chinese patent CN202310361471.4 discloses a hydrophobically modified zeolite molecular sieve and its preparation method and application. The composition of the molecular sieve includes a zeolite molecular sieve and a fluorinated carbon layer coated thereon; the thickness of the fluorinated carbon layer is 2 to 6 microns; the mass of the fluorinated carbon is 5% to 60% of the mass of the zeolite molecular sieve; in the preparation, a layer of organic polymer containing fluorine functional groups is coated on the surface of the zeolite molecular sieve by simple impregnation and carbonization, and a uniform and stable fluorinated carbon hydrophobic layer is obtained after calcination. The preparation method of the present invention is simple, has a short cycle, and has a large output, and is suitable for large-scale industrial development; compared with other hydrophobic modified molecular sieves, the fluorinated carbon-coated zeolite molecular sieve has the advantages of easy regeneration and good repeated stability. This patent uses fluoride as a raw material, and F ions can corrode metal containers and cause environmental pollution.
[0004] Chinese patent CN202211318208.9 discloses a highly hydrophobic mesoporous Y-type molecular sieve and its preparation method, which belongs to the field of hydrophobic molecular sieve technology. The highly hydrophobic mesoporous Y-type molecular sieve has a pore size of more than 2nm, a mesoporous structure, a unit cell parameter range of 24.20~24.35Å, a silicon-aluminum ratio of less than 80, a water absorption rate of less than 5%, and a phosphorus content of 0.1~1%; by phosphorus-modified NaY molecular sieve, the acidity of the molecular sieve is adjusted to improve the stability of the skeleton; by treating with high-temperature acid steam in an oxygen-free environment, the dealumination, mesopore formation, and unit cell shrinkage are carried out simultaneously, which can shorten the process flow, greatly reduce the amount of organic acid, and will not cause the problem of molecular sieve skeleton collapse; use weak base to neutralize the free acid on the surface of the molecular sieve, remove the free aluminum and sodium ions on the surface and pores of the molecular sieve, and quickly shrink the unit cell through high-temperature hydrothermal treatment, combined with high-temperature calcination treatment, reduce the acidity of the molecular sieve, thereby improving the hydrophobic performance of the product. The present invention uses high-temperature acid vapor, and the acid at high temperature will corrode the material, causing a significant increase in production costs.
[0005] Although Y-type molecular sieves have multiple uses, existing Y-type molecular sieves have the problems of strong water absorption, many acid sites, low specific surface area and overly large pore size. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a super hydrophobic Y-type molecular sieve, wherein the prepared Y-type molecular sieve is economical and efficient, has strong hydrophobicity, high specific surface area, and moderate pore size. The present invention greatly reduces the water absorption of the Y-type molecular sieve after secondary calcination. The hydrophobicity of the molecular sieve is improved under the condition of low silicon-aluminum ratio, which not only retains the large surface area and pore size of the molecular sieve, but also can solve the pollution and high cost caused by the organosilane modification, and avoids the corrosion of F ions to metal containers and the pollution of the environment. And the process is simple, the raw materials are cheap and easy to obtain, and it is suitable for large-scale industrial production.
[0007] The method for preparing the super hydrophobic Y-type molecular sieve of the present invention comprises the following steps:
[0008] (1) Mix the acidic solution and NaY molecular sieve in a solid-liquid mass ratio of 1 to 10:1, stir at 20 to 90 °C for 0.5 to 5.0 h, filter, and wash with water until the pH is 4.0 to 8.0;
[0009] (2) mixing the product obtained in step (1) with a rare earth solution in a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90° C. for 0.5 to 5.0 h, filtering, washing with water until the pH value is 4.0 to 8.0, drying and then crushing;
[0010] (3) roasting the product prepared in step (2) at a certain steam space velocity for a period of time;
[0011] (4) mixing the product prepared in step (3) with an acidic solution in a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90°C for 0.5 to 5.0 hours, filtering, and washing with water until the pH value is 4.0 to 8.0;
[0012] (5) preparing an iron-copper solution according to a mass ratio of iron ions, copper ions and water of 1: 0.01-10: 10-100;
[0013] (6) mixing the solution prepared in step (5) with the product prepared in step (4) at a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90° C. for 0.5 to 5.0 h, filtering, washing, drying, and then crushing;
[0014] (7) The product obtained in step (6) is calcined at a certain temperature to obtain a super hydrophobic Y-type molecular sieve.
[0015] Wherein, the acidic solution in step (1) is an inorganic acid solution, an acid salt solution or a mixed solution of an inorganic acid and an acid salt.
[0016] The inorganic acid is one or more of sulfuric acid, hydrochloric acid or nitric acid; the acid salt is one or more of ammonium sulfate, ammonium chloride or ammonium nitrate; in the mixed solution of the inorganic acid and the acid salt, the inorganic acid or the acid salt is mixed in any proportion, and the pH of the mixed solution is 1.0~6.0.
[0017] The acidic solution plays the role of exchanging Na+ ions and dealumination.
[0018] The rare earth solution in step (2) is one or more of lanthanum chloride solution, lanthanum nitrate solution, cerium chloride solution or cerium nitrate solution.
[0019] The concentration of rare earth solution is 0.05mol / L~0.5mol / L.
[0020] The product in step (3) is calcined at a temperature of 300-700°C; the calcination time is 0.5-5.0h; and the water vapor mass space velocity is 0.5-2h -1 .
[0021] The calcination temperature of the product in step (3) is 500-650°C; the calcination time is 1-3h.
[0022] The acidic solution in step (4) is one or more of oxalic acid, citric acid or phosphoric acid solution.
[0023] The solution containing iron ions in step (5) is one or more of ferrous oxalate, ferric sulfate, ferric chloride or ferric nitrate; the solution containing copper ions is one or more of copper sulfate, copper chloride, copper nitrate or copper acetate.
[0024] The calcination temperature in step (7) is 500-1000°C; the calcination time is 0.5-3h.
[0025] The calcination temperature in step (7) is 550°C to 850°C; the calcination time is 1 to 2 hours.
[0026] The invention firstly treats the NaY molecular sieve with an acid solution and a rare earth solution, then performs a hydrothermal calcination on the treated sample, and finally obtains the super-hydrophobic Y-type molecular sieve through acid exchange, iron and copper ion loading and calcination.
[0027] The prior art uses acid solution and rare earth solution to exchange the modified Y molecular sieve, which contains more acid sites and has a larger pore size, which inevitably makes it have high water absorption performance. The treatment method of the present invention is to first reduce the metal cations with smaller size contained in the molecular sieve, increase the size of the metal cations by rare earth exchange and roasting, reduce the unit cell to fix it inside the molecular sieve, and reduce the acid sites of the molecular sieve; secondly, the mixed exchange of iron ions and copper ions further occupies the internal pores of the molecular sieve to remove free aluminum elements, and finally reduce the number of hydroxyl groups at the acid sites by high temperature roasting, reduce the pore size, and change Si-O-Al to Si-O-Si, thereby greatly improving the hydrophobic performance.
[0028] The present invention does not use organic solvents for silanization treatment, thereby reducing the pollution to water resources and the pressure on the atmospheric environment caused by subsequent treatment with organic solvents.
[0029] The method uses an acidic solution combined with rare earth to reduce the acidity of the Y-type molecular sieve and utilize rare earth ions to occupy the molecular sieve pores; the position of the rare earth ions in the pores is stabilized through hydrothermal calcination; iron and copper ions are loaded at a certain ratio, and the acidity of the Y-type molecular sieve after secondary loading is further reduced, and the pores are further occupied; after secondary calcination, the water absorption of the Y-type molecular sieve can be greatly reduced, thereby achieving the purpose of super hydrophobicity.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention can improve the hydrophobicity of the molecular sieve under the condition of low silicon-aluminum ratio, which not only retains the large surface area and pore size of the molecular sieve, but also solves the pollution and high cost problems caused by organic silane modification, thereby achieving super hydrophobicity.
[0032] The super hydrophobic Y-shaped molecular sieve of the invention is economical and efficient, has strong hydrophobicity, high specific surface area and moderate pore size.
[0033] The present invention does not use fluoride, thus avoiding the corrosion of metal containers and the pollution of the environment by F ions.
[0034] The present invention does not use high-temperature acid vapor, thus avoiding acid corrosion to materials at high temperatures, thereby increasing production costs. In addition, the present invention still has excellent hydrophobic properties without generating mesopores that cause instability in the molecular sieve skeleton structure, and still has advantages over its water absorption rate of 5%.
[0035] The invention has a simple process, cheap and readily available raw materials, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] Add 1200g of 1.0mol / L ammonium sulfate solution into a 2000mL beaker, heat it to 70℃ in a water bath, add 300.0g of NaY molecular sieve, stir it in a water bath for 1h, cool it down quickly to room temperature, filter it, wash it, wash the filter cake with water until pH=5; get 580g of filter cake, add 1200g of 0.1mol / L lanthanum chloride solution into a 2000mL beaker, put the washed filter cake in it, stir it evenly, heat it to 70℃ in a water bath, keep it at constant temperature for 1h, cool it down quickly to room temperature, filter it, wash it until pH value reaches 6.0, dry it in an oven at 120℃ for 12h, and then crush it. 200.0g of the crushed sample is placed in a steam mass space velocity of 1.0h -1 , calcined at 600℃ for 2.0h; 800g of 0.5mol / L oxalic acid solution was added to a 1000mL beaker, and 200.0g of the hydrothermal treatment sample was added after the water bath was heated to 70℃, and the sample was stirred in the water bath for 1h before filtering and washing to a pH of 4.0; 400g of 0.01mol / L ferrous oxalate solution and 400g of 0.01mol / L cupric acetate solution were added to a 1000mL beaker, and 200.0g of the treated sample was added after the water bath was heated to 80℃, and the sample was stirred in the water bath for 1h before filtering and washing to a pH of 6, and the sample was dried in an oven at 120℃ for 12h and then crushed; the crushed sample was calcined at 800℃ for 1.0h to obtain a sample, and the obtained sample was a superhydrophobic Y-type molecular sieve.
[0039] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), its water absorption rate was measured to be 5.88%.
[0040] Example 2
[0041] Add 600g of 0.5mol / L ammonium chloride solution into a 1000mL beaker, heat it to 50℃ in a water bath, add 100.0g of NaY molecular sieve, stir it in a water bath for 0.5h, cool it down quickly to room temperature, filter it, wash it, wash the filter cake with water until pH=6; get 190g of filter cake, add 600g of 0.07mol / L lanthanum nitrate solution into a 1000mL beaker, put the washed filter cake in, stir it evenly, heat it to 60℃ in a water bath, keep it at constant temperature for 1h, cool it down quickly to room temperature, filter it, wash it until pH value reaches 5.0, dry it in an oven at 120℃ for 12h, and then crush it. 70.0g of the crushed sample is placed in a steam mass space velocity of 1.5h -1 , calcined at 500℃ for 3.0h. Add 400g of 0.5mol / L citric acid solution to a 1000mL beaker, heat it to 70℃ in a water bath, add 50.0g of the hydrothermal treatment sample, stir it in a water bath for 1h, filter it, and wash it with water until pH=5; add 200g of 0.01mol / L ferric nitrate solution and 200g of 0.01mol / L copper nitrate solution to a 500mL beaker, heat it to 60℃ in a water bath, add 50.0g of the treatment sample, stir it in a water bath for 1h, filter it, wash it, wash the filter cake with water until pH=8, dry it in an oven at 120℃ for 12h, and then crush it; the crushed sample is calcined at 700℃ for 2.0h to obtain the superhydrophobic Y-type molecular sieve.
[0042] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), its water absorption rate was measured to be 7.31%.
[0043] Example 3
[0044] 800g of 1.0mol / L ammonium nitrate solution was added to a 1000mL beaker, heated to 80℃ in a water bath, and then 200.0g of NaY molecular sieve was added. The mixture was stirred in a water bath for 1.0h, and then quickly cooled to room temperature and filtered and washed. The filter cake was washed with water until pH=8; 384g of filter cake was obtained, and 800g of 0.1mol / L cerium chloride solution was added to a 1000mL beaker, and the washed filter cake was placed in the beaker and stirred evenly. The mixture was heated to 70℃ in a water bath, and kept at a constant temperature for 0.5h. The mixture was quickly cooled to room temperature and filtered. The filter cake was washed until the pH value reached 7.0, and then placed in an oven at 120℃ for 12h and then crushed. 100.0g of the crushed sample was precipitated at a water vapor mass space velocity of 1.0h -1, calcined at 550℃ for 1.5h. Add 500g of 0.05mol / L phosphoric acid solution to a 1000mL beaker, heat it to 70℃ in a water bath, add 100.0g of the hydrothermal treatment sample, stir it in a water bath for 2h, filter it, wash it, and wash it with water until pH=7; add 300g of 0.03mol / L ferric chloride solution and 100g of 0.02mol / L cupric chloride solution to a 500mL beaker, heat it to 80℃ in a water bath, add 100.0g of the treated sample, stir it in a water bath for 2.0h, filter it, wash it, wash it with water until pH=7, dry it in an oven at 120℃ for 12h, and then crush it; the crushed sample is calcined at 600℃ for 3.0h to obtain the superhydrophobic Y-type molecular sieve.
[0045] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), the water absorption rate was measured to be 8.53%.
[0046] Example 4
[0047] 400g of 1.0mol / L ammonium nitrate solution and 400g of 1.0mol / L sulfuric acid solution were added to a 1000mL beaker, heated to 70℃ in a water bath, and then 200.0g of NaY molecular sieve was added. The mixture was stirred in a water bath for 1.0h, and then the mixture was rapidly cooled to room temperature and filtered and washed. The filter cake was washed with water until pH=7. 380g of filter cake was obtained, and 800g of 0.1mol / L lanthanum chloride solution was added to a 1000mL beaker. The washed filter cake was placed in the beaker and stirred evenly. The mixture was heated to 80℃ in a water bath, and kept at a constant temperature for 0.8h. The mixture was rapidly cooled to room temperature and filtered. The mixture was washed until the pH value reached 6.0. The mixture was dried in an oven at 120℃ for 12h and then crushed. 100.0g of the crushed sample was precipitated at a water vapor mass space velocity of 1.0h -1 , calcined at 550℃ for 1.5h. Add 500g of 0.05mol / L phosphoric acid solution to a 1000mL beaker, heat it to 70℃ in a water bath, add 100.0g of the hydrothermal treatment sample, stir it in a water bath for 2h, filter it, wash it, and wash it with water until pH=8; add 300g of 0.03mol / L ferric chloride solution and 100g of 0.02mol / L copper chloride solution to a 500mL beaker, heat it to 80℃ in a water bath, add 100.0g of the treated sample, stir it in a water bath for 2.0h, filter it, wash it, wash it with water until pH=6, dry it in an oven at 120℃ for 12h, and then crush it; the crushed sample is calcined at 600℃ for 3.0h to obtain the superhydrophobic Y-type molecular sieve.
[0048] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), its water absorption rate was measured to be 5.81%.
[0049] Example 5
[0050] 1200g of 1.0mol / L ammonium chloride solution and 400g of 1.0mol / L sulfuric acid solution were added to a 2000mL beaker, heated to 75°C in a water bath, and then 300.0g of NaY molecular sieve was added. The mixture was stirred in a water bath for 1.0h, and then the mixture was rapidly cooled to room temperature and filtered and washed. The filter cake was washed with water until pH=4. 584g of filter cake was obtained. 1000g of 0.1mol / L lanthanum chloride solution was added to a 2000mL beaker, and the washed filter cake was placed in the beaker and stirred evenly. The mixture was heated to 70°C in a water bath, and kept at a constant temperature for 1h. The mixture was rapidly cooled to room temperature and filtered. The mixture was washed until the pH value reached 7.0. The mixture was dried in an oven at 120°C for 12h and then crushed. 200.0g of the crushed sample was precipitated at a water vapor mass space velocity of 2.0h -1 , calcined at 550℃ for 1.5h. 800g of 0.05mol / L phosphoric acid solution was added to a 2000mL beaker, heated to 80℃ in a water bath, and then 200.0g of the hydrothermal treatment sample was added. After stirring in a water bath for 2h, the sample was filtered, washed, and washed with water until pH=7; 300g of 0.03mol / L ferric chloride solution and 100g of 0.02mol / L cupric chloride solution were added to a 500mL beaker, heated to 80℃ in a water bath, and then 200.0g of the treated sample was added. After stirring in a water bath for 2.0h, the sample was filtered, washed, and washed with water until pH=6, placed in an oven at 120℃ for 12h, and then crushed; the crushed sample was roasted at 600℃ for 3.0h to obtain a superhydrophobic Y-type molecular sieve.
[0051] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), its water absorption rate was measured to be 6.51%.
[0052] Example 6
[0053] 800g of 0.5mol / L nitric acid solution was added to a 1000mL beaker, heated to 50℃ in a water bath, and then 100.0g of NaY molecular sieve was added. The mixture was stirred in a water bath for 0.5h, and then quickly cooled to room temperature and filtered and washed. The filter cake was washed with water until pH=7; 187g of filter cake was obtained, 600g of 0.07mol / L lanthanum nitrate solution was added to a 1000mL beaker, and the washed filter cake was placed in the beaker and stirred evenly. The mixture was heated to 60℃ in a water bath, and kept at a constant temperature for 1h. The mixture was quickly cooled to room temperature and filtered. The mixture was washed until the pH value reached 6.0, and then dried in an oven at 120℃ for 12h and then crushed. 70.0g of the crushed sample was heated to 1h at a water vapor mass space velocity of 1h. -1, calcined at 600℃ for 3.0h. Add 400g of 0.5mol / L citric acid solution to a 1000mL beaker, heat it to 70℃ in a water bath, add 50.0g of the hydrothermal treatment sample, stir it in a water bath for 1h, filter it, and wash it with water until pH=6; add 200g of 0.01mol / L ferric nitrate solution and 200g of 0.01mol / L copper nitrate solution to a 500mL beaker, heat it to 60℃ in a water bath, add 50.0g of the treatment sample, stir it in a water bath for 1h, filter it, wash it, wash the filter cake with water until pH=7, dry it in an oven at 120℃ for 12h, and then crush it; the crushed sample is calcined at 700℃ for 2.0h to obtain the superhydrophobic Y-type molecular sieve.
[0054] According to the molecular sieve static water adsorption determination method (GBT_6287-2021), its water absorption rate was measured to be 6.43%.
[0055] Table 1 shows the physical properties of the products obtained in Examples 1-6 and Comparative Example 1, wherein the sample in Comparative Example 1 is a commercially available hydrophobic Y-type molecular sieve having a silicon-aluminum ratio of 67.9, a unit cell parameter of 24.31, and a relative crystallinity of 72%.
[0056] Table 1 shows the physical properties of the products obtained in Examples 1-6 and the product obtained in Comparative Example 1
[0057]
Claims
1. A method for preparing a super hydrophobic Y-type molecular sieve, characterized in that: The preparation method of super hydrophobic Y-type molecular sieve comprises the following steps: (1) Mix the acidic solution and NaY molecular sieve in a solid-liquid mass ratio of 1 to 10:1, stir at 20 to 90 °C for 0.5 to 5.0 h, filter, and wash with water until the pH is 4.0 to 8.0; (2) mixing the product obtained in step (1) with a rare earth solution in a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90° C. for 0.5 to 5.0 h, filtering, washing with water until the pH value is 4.0 to 8.0, drying and then crushing; (3) roasting the product prepared in step (2) at a certain steam space velocity for a period of time; (4) mixing the product prepared in step (3) with an acidic solution in a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90°C for 0.5 to 5.0 hours, filtering, and washing with water until the pH value is 4.0 to 8.0; (5) preparing an iron-copper solution according to a mass ratio of iron ions, copper ions and water of 1: 0.01-10: 10-100; (6) mixing the solution prepared in step (5) with the product prepared in step (4) at a solid-liquid mass ratio of 1:1 to 10, stirring at 20 to 90° C. for 0.5 to 5.0 h, filtering, washing, drying, and then crushing; (7) The product obtained in step (6) is calcined at a certain temperature to obtain a super hydrophobic Y-type molecular sieve.
2. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The acidic solution in step (1) is an inorganic acid solution, an acid salt solution or a mixed solution of an inorganic acid and an acid salt.
3. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 2, characterized in that: The inorganic acid is one or more of sulfuric acid, hydrochloric acid or nitric acid; the acid salt is one or more of ammonium sulfate, ammonium chloride or ammonium nitrate; in the mixed solution of the inorganic acid and the acid salt, the inorganic acid or the acid salt is mixed in any proportion, and the pH of the mixed solution is 1.0~6.
0.
4. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The rare earth solution in step (2) is one or more of lanthanum chloride solution, lanthanum nitrate solution, cerium chloride solution or cerium nitrate solution.
5. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The product in step (3) is calcined at a temperature of 300-700°C; the calcination time is 0.5-5.0h; and the water vapor mass space velocity is 0.5-2h -1 .
6. The method for preparing the super hydrophobic Y-type molecular sieve according to claim 5, characterized in that, The product in step (3) is calcined at a temperature of 500-650°C for a time of 1-3 hours.
7. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The acidic solution in step (4) is one or more of oxalic acid, citric acid or phosphoric acid solution.
8. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The solution containing iron ions in step (5) is one or more of ferrous oxalate, ferric sulfate, ferric chloride or ferric nitrate; the solution containing copper ions is one or more of copper sulfate, copper chloride, copper nitrate or copper acetate.
9. The method for preparing a super hydrophobic Y-type molecular sieve according to claim 1, characterized in that: The calcination temperature in step (7) is 500-1000°C; the calcination time is 0.5-3h.
10. The method for preparing the super hydrophobic Y-type molecular sieve according to claim 9, characterized in that: The calcination temperature in step (7) is 550°C to 850°C; the calcination time is 1 to 2 hours.
Citation Information
Patent Citations
A highly hydrophobic mesoporous Y-type molecular sieve and its preparation method
CN115594193B
Hydrophobic modified zeolite molecular sieve as well as preparation method and application thereof
CN116237011A
Rare earth-containing Y molecular sieve and preparation method thereof
CN107970969A